Annual Address to the Board of Governors, September 7, 1964 - Woods, George D. (World Bank, Washington, DC, 2019)
George D. Woods, President of the World Bank and its affiliates, spoke about Japan as a vibrant example of both reconstruction and development. He briefly reported on developments in the World Bank Group of institutions during the past year, including partnership agreements with the U.N. Food and Agriculture Organization and UNESCO. He indicated some of the principal preoccupations in the period ahead, such as a scarcity of good projects to support, large debt service burdens, and the next IDA replenishment. Finally, he concluded by saying a few words about developments in the world environment in which the Bank group operates and about the possible effect of those developments upon the role of the organizations.